Cocrystal approach to modulate the photoluminescent properties of a GFP chromophore analogue: role of halogen/hydrogen bonding in achieving a wide range of solid-state fluorescence emissions - Mali, Bhupendra P.; Dash, Soumya Ranjan; Annadhasan, Mari; Biswas, Anupam; Manoj, Kochunnoonny; Vanka, Kumar; Gonnade, Rajesh G. (Crystal Growth & Design, 2023)
Fine-tuning the photophysical properties of fluorescentorganicsolids is essential to attain multicolor displays and meet the demandfor futuristic light-emitting materials. Here, we report the tunableluminescence of a green fluorescent protein (GFP) chromophore analogue,3,4,5-TIA (A), based on the formation of two-component molecular cocrystalswith six different coformers. Coformers selected to synthesize thebinary cocrystals include 1,4-diiodotetrafluorobenzene (B), perfluoronaphthalene(C), 1,4-dibromotetrafluorobenzene (D), 2,3,5,6-tetrafluoroterephthalicacid (E), benzene-1,2,4,5-tetracarbonitrile (F), and benzene-1,2,4,5-tetracarboxylicacid (G). Interestingly, the cocrystals A center dot C and A center dot Fshowed molecular crystal polymorphism with a slight variation in fluorescence,revealing an aggregation-induced emission (AIE). A crystal structureanalysis showed the interplay of hydrogen bonding, halogen bonding,and aromatic pi-stacking interactions in associating neutralsolid components in the cocrystal. All of the novel cocrystals displayeda wide range of photoluminescence ranging from blue to dark orange.The time-dependent density functional theory (TD-DFT) calculationsindicate the changes in the energy level structures (HOMO to LUMO)in cocrystals that resulted in variations in fluorescence emission.The study aims to further understand the structure-propertyrelationship between molecular arrangement and photoluminescence. Cocrystals of a GFPc analogue with differentcoformers displayeda wide range of fluorescence emissions ranging from blue to dark orangewith varying quantum yields. With similar geometries of pi-stackinginteractions, hydrogen and halogen bonding have played a vital rolein fine-tuning the photoluminescence; halogen bonding leads to a blueshift, and hydrogen bonding results in a red shift.